Identification of Fault Structure in the Vicinity of Bukik Gadang Hot Spring Mount Talang Subdistrict Using Geomagnetic Method - Ikhwan Fikri Maulidan; Marzuki Marzuki; Ardian Putra (Postgraduate, University of Mataram, 2022)
Geological structures in the Bukit Gadang geothermal area have been identified using the geomagnetic method to determine the type of fault. Data was measured using a magnetometer in the area with dimensions of 1200 m × 1200 m consisting of 144 points at 12 tracks, and the spacing between points was 100 m. Magnetic anomaly data performed diurnal and IGRF (International Geomagnetic Reference Field) corrections. Furthermore, reduced to poles and continuous upwards processes were carried out to remove noise and separate local and regional anomalies. The magnetic field anomaly ​​in the study area ranges from -1771.8 nT to 1089.9 nT, dominated by negative values, indicating the presence of heat sources and the influence of demagnetization of subsurface rocks. The 2D modeling results show that two primary rocks dominate the study area; pyroclastic flow units and andesite lava rock, which come from the Jantan and Batino volcanic formations. The caprock rock layer was identified in the upper layer with a depth of 850 meters. The reservoir rock layer with low susceptibility values ​​was below the caprock layer. The 3D modeling results show a normal fault with a depth of 300-800 meters or at the border of the Jantan volcanic formation with the Batino volcanic formation. The fault line leads to the southeast-northwest (N160°E). The faults obtained from the 2D and 3D models are suspected to be the outflow of geothermal fluid from the reservoir rock layer and form a manifestation in the form of a hot spring at Bukik Gadang.